A prospective, controlled clinical evaluation of surgical stabilization of severe rib fractures. Issue 2 (February 2016) - Pieracci, Fredric M.; Lin, Yihan; Rodil, Maria; Synder, Madelyne; Herbert, Benoit; Tran, Dong Kha; Stoval, Robert T.; Johnson, Jeffrey L.; Biffl, Walter L.; Barnett, Carlton C.; Cothren-Burlew, Clay; Fox, Charles; et al.
Abstract : BACKGROUND: Previous studies of surgical stabilization of rib fractures (SSRF) have been limited by small sample sizes, retrospective methodology, and inclusion of only patients with flail chest. We performed a prospective, controlled evaluation of SSRF as compared with optimal medical management for severe rib fracture patterns among critically ill trauma patients. We hypothesized that SSRF improves acute outcomes. METHODS: We conducted a 2-year clinical evaluation of patients with any of the following rib fracture patterns: flail chest, three or more fractures with bicortical displacement, 30% or greater hemithorax volume loss, and either severe pain or respiratory failure despite optimal medical management. In the year 2013, all patients were managed nonoperatively. In the year 2014, all patients were managed operatively. Outcomes included respiratory failure, tracheostomy, pneumonia, ventilator days, tracheostomy, length of stay, daily maximum incentive spirometer volume, narcotic requirements, and mortality. Univariate and multivariable analyses were performed. RESULTS: Seventy patients were included, 35 in each group. For the operative group, time from injury to surgery was 2.4 day, operative time was 1.5 hours, and the ratio of ribs fixed to ribs fractured was 0.6. The operative group had a significantly higher RibScore (4 vs. 3, respectively, p < 0.01) and a significantly lower incidence of intracranial hemorrhage (5.7% vs. 28.6%, respectively, p = 0.01). After controlling for these differences, the operative group had a significantly lower likelihood of both respiratory failure (odds ratio, 0.24; 95% confidence interval, 0.06–0.93; p = 0.03) and tracheostomy (odds ratio, 0.18; 95% confidence interval, 0.04–0.78; p = 0.03). Duration of ventilation was significantly lower in the operative group ( p < 0.01). The median daily spirometry value was 250 mL higher in the operative group ( p = 0.04). Narcotic requirements were comparable between groups. There were no mortalities. CONCLUSION: In this evaluation, SSRF as compared with the best medical management improved acute outcomes among a group of critically ill trauma patients with a variety of severe fracture patterns. LEVEL OF EVIDENCE: Therapeutic study, level II. Abstract : Supplemental digital content is available in the text.